INTERNAL СONTROL OF THE TOUR OPERATOR AS A BUSINESS FUNCTION OF ITS CONTROL SYSTEM - ALIYA Gizyatova (Учёт. Анализ. Аудит)
The sustainability of the tour operators’ activity is the basis of this industry stability. In recent years, the crisis in the tourism industry manifested by a series of bankruptcies of major tour operators became apparent due to the fact that it badly affected a large number of Russian tourists, and this, in turn, caused a great resonance in the society. Development and promotion of travel products is private business. Under market conditions implementing of internal control within the management system of the tourist industry is an additional instrument of providing for financial and economic stability. The purpose of the article is to justify the necessity to formalize the approaches to tour operator internal control system functioning on the basis of the Russian legal requirements and international experience, which is mostly demanded in the frames of the risk-based government oversight. The theoretical basisof the research is the papers of economists on the related problems. The empirical base for the study is the Russian normative acts and international practice.